Pre-pandemic artificial MERS analog of polyfunctional SARS-CoV-2 S1/S2 furin cleavage site domain is unique among spike proteins of genus Betacoronavirus - Andreas Martin Lisewski (BMC Genomic Data)
Abstract Objectives SARS-CoV-2 spike (S) glycoprotein furin cleavage site is a key determinant of SARS-CoV-2 virulence and COVID-19 pathogencity. Located at the S1/S2 junction, it is unique among sarbecoviruses but frequently found among betacoronaviruses. Recent evidence suggests that this site includes two additional functional motifs: a pat7 nuclear localization signal and two flanking O-glycosites. However, a systematic genus and subgenus analysis of spike protein sequences bearing this polyfunctional sequence domain has been missing. Data description Here we report comprehensive sequence data to demonstrate that among spike proteins of genus Betacoronavirus and outside of the SARS-CoV-2 clade a fully analogous S1/S2 domain was found in only one other virus: the artificial MERS infectious clone MERS-MA30, described already in 2017, which was rationally selected from serial passage in genetically humanized mice. As the evolutionarily closest betacoronaviruses outside of the SARS-CoV-2 clade lack all its three functional motifs, these data extend—beyond natural evolution and zoonosis—the current view on SARS-CoV-2 pre-pandemic origins by presenting the analogous S1/S2 MERS-MA30 sequence domain as a precise molecular blueprint for SARS-CoV-2.